A representação da loucura em ermos e gerais - Oliveira, Elis Regina da Silva (2011)
Insanity as social object, is composed by a discourse networking, that have outlined a broad way in arts in general and specially in literature. Many writers from the national canon performed the esthetics crossing by the insanity route and have been legated to the universe of the exciting letters reflections about the insanity phenomenon. Bernardo Élis makes part of this group, and by the way, the Brazilian writer exposed the signs of the hard reality experienced by the man who lived in the wilds of Brazil and with this consolidated artistically the insanity fate as a key element of interpretation of small goianas communities in mid-century XX. So, esthetically represented, the insanity becomes to be the metaphor of spoiled identity and the madman, by his time, becomes to be the difference subject. Following also in this way, with this study intends to reflect about of numerous speeches socially constructed in relation to the insane person and the insane representation in some tales from Ermos e Gerais (1944), namely: “O louco da sombra”, “A virgem santíssima do quarto de Joana”, “André Louco”. From the analysis of language, observation of the antics narrator, and the composition of character, whose objective is to find if the literary text protects itself as space of emancipation, knowledge of each other from themselves, or, reinforces the negatives stereotypes of the socially marginalized groups. For this agreement, this study will base on philosophic assumptions from Michel Foucault about the insanity.